Excellent high-temperature piezoelectric energy harvesting properties in flexible polyimide/3D PbTiO3 flower composites. (April 2021) - Jian, Gang; Jiao, Yong; Meng, Qingzhen; Guo, Yuhang; Wang, Fengwei; Zhang, Jiaqi; Wang, Cheng; Moon, Kyoung-Sik; Wong, Ching-Ping
Abstract: Piezoelectric nanogenerators (PENGs) have been paid great attention in powering electronics via harvesting mechanical energy. Presently, increasing lights are shed onto flexible PENGs capable of working at harsh temperatures. In this research, we report a synthesis of 3D hierarchical PbTiO3 flower-like structure (PTFs) and polyimide (PI)/PTFs composites from which PENGs with excellent high-temperature energy harvesting performances are fabricated. PTFs exhibit a pure phase and a 3D architecture obtained by the hydrothermal method. The PI/PTFs composite PENGs exhibit good electricity-generation performances of Voc ~ 140 V, Isc ~ 103 μA and P ~ 2128 μW. Moreover, high degree of electric power can be continuously generated by the PENG at a wide range of temperature from room-temperature to 300 °C. Excellent durability up to 5000 cycles can be also obtained for the PENG within the temperature range. It has been demonstrated that a PENG in this study lights fifty light-emitting diodes and the resulting electricity is successfully stored in a capacitor. In addition, a real-time high-temperature application is presented where harvesting electricity via the vibration energy of the running automobile engine occurs. The outstanding piezoelectric performance of PENG in this study is attributed to the thermal stability of PI and PT materials, and unique 3D architectures of PTFs in the composites. This work reveals a PI/PTFs composite based PENG exhibiting excellent energy harvesting properties at high-temperatures and the potential applications as microenergy harvesters. Graphical Abstract: ga1 Highlights: PI/PTFs PENG is prepared as a flexible high-temperature piezoelectric microenergy harvester. The PENG generates Voc ~ 140 V, Isc ~ 103 μA and P ~ 2128 μW at room temperature. The PENG exhibits good energy harvesting properties and good stability from room temperature to 300 °C. Flower morphology is crucial for the excellent performances of the PENG due to the high local stress and local heat flux. A real-time high temperature application is presented as the PENG harvests vibrations on a running automobile engine.